Principals' Strategic Planning and School Effectiveness in Public Senior Secondary Schools, Kwara State, Nigeria - Adeseko Sunday Olaifa; Nafisat Omolara YEKEEN; Muritala Adaramaja SHEU; Oluwaseyi Godwin ARE; Olaide Abidemi NIJI-OLAWEPO (PGRI University Yogyakarta, 2026)
This study investigated the relationship between principals' strategic planning and school effectiveness in public senior secondary schools in Kwara State, Nigeria. Four dimensions of principals' strategic planning goal-setting, resource management planning, data-driven planning, and communication planning were examined in relation to key indicators of school effectiveness, namely student academic achievement, teacher effectiveness, and parent and community satisfaction. A correlational survey design was adopted. The population comprised principals and teachers in the 413 public senior secondary schools in Kwara State, and a multi-stage sampling technique yielded 203 usable responses from 275 administered copies of the self-designed Principals' Strategic Planning and School Effectiveness Questionnaire (PSPSEQ), which recorded a Cronbach's alpha reliability coefficient of 0.81. Data were analysed using mean, standard deviation, and Pearson Product-Moment Correlation (PPMC) at the 0.05 level of significance. Results showed that principals engaged moderately to highly in all four strategic planning dimensions (overall mean = 3.21, SD = 0.614) and that school effectiveness was generally high (mean = 3.34, SD = 0.667). A significant positive relationship was found between overall strategic planning and school effectiveness (r = .393, p < .05), and each of the four dimensions — goal-setting planning (r = .569), resource management planning (r = .255), data-driven planning (r = .386), and communication planning (r = .507) was significantly related to school effectiveness. The study concludes that strengthening principals' strategic planning practices is essential for sustainable school improvement and recommends targeted capacity-building, stakeholder engagement, and data-driven decision-making in public secondary schools. Keywords: Strategic Planning, School Effectiveness, Goal Setting, Resource Management, Data-Driven Planning, Communication Planning